President's Message - Knight, Mary (Operating Room Nurses Association of Canada Journal, 2002)
A recurring theme in recent publications, conferences and in the news is the presence of abuse or violence in the healthcare environment. Several sessions at the World Conference on Surgical Patient Care last September addressed this topic, including submissions from New Zealand, Finland and Australia. Sadly, workplace violence or harassment appears to be a global phenomenon.